Risk Factors for Renal Impairment in Adult Patients With Short Bowel Syndrome - Wang, Peng; Yang, Jianbo; Zhang, Yupeng; Zhang, Li; Gao, Xuejin; Wang, Xinying (Frontiers in Nutrition, 2021)
Renal impairment is a common complication in patients with intestinal failure that is mostly caused by short bowel syndrome (SBS) and is associated with adverse outcomes that severely affect the quality of life or even survival. The prevalence and risk factors for renal impairment in patients with SBS remain unclarified. Therefore, we aimed to determine the prevalence of renal impairment and identify potential risk factors for renal impairment in adult patients with SBS. We retrospectively identified 199 patients diagnosed with SBS admitted to the Department of General Surgery between January 1 2012 and January 1, 2019, from a prospectively maintained database. Overall, 56 patients (28.1%) with decreased renal function (eGFR<90ml/min/1.73m2). The median duration of SBS was 7 months (IQR, 3-31 months) and the mean eGFR was 103.1 ± 39.4 mL/min/1.73 m2. Logistic regression modelling indicated that older age (odds ratio (OR), 1.074; 95% CI, 1.037–1.112, p <0.001), kidney stones (OR, 4.887; 95% CI, 1.753–13.626; p = 0.002), decreased length of the small intestine (OR, 0.988; 95% CI, 0.979–0.998; p = 0.019), and prolonged duration of SBS (OR, 1.007; 95% CI, 1.001–1.013; p = 0.046) were significant risk factors for renal impairment. This is the largest study that has specifically explored the risk factors for renal impairment in a large cohort of adults with SBS. The present study showed that renal function should be closely monitored during treatment, and patients should be given prophylactic interventions if necessary. This retrospective study is a part of clinical study NCT03277014, registered in ClinicalTrials.gov PRS. And the PRS URL is http://register.clinicaltrials.gov